A new species and a new name in Myrtaceae (Myrteae) from Southeastern Brazil - Proença, Carolyn E. B.; Faria, Jair Eustáquio Quintino; Mazine, Fiorella Fernanda (Phytotaxa, 2017)
This paper describes a new species of Eugenia and proposes a new name in Psidium, from Southeastern Brazil. Both are necessary for a floristic treatment of Myrtaceae for the flora of São Paulo, Brazil. Eugenia robustior is most similar to Eugenia tetramera from which it differs by its larger leaves and flowers with more stamens and more ovules per locule. The new name in Psidium is a replacement name for the illegitimate P. sellowianum.